Pendampingan Pasar Tradisional Menuju Pasar Sehat Di Kecamatan Mengwi Kabupaten Badung - Suyasa, I Nyoman Gede; Rusminingsih, Ni Ketut (Jurnal Pengabmas Masyarakat Sehat, 2024)
The traditional market in Mengwi District is managed under the traditional village and is an asset for the customary village concerned. Traditional markets in Mengwi District include the Penarungan Traditional Village market, the Gulingan Traditional Village market, the Mengwi Traditional Village market, the Mengwitani Traditional Village Market, the Buduk Traditional Village Market, the Munggu Traditional Village Market and the Br Sayan Traditional Village Market. The products sold include meat, fish, vegetables, fruit, dry and wet food, ready-to-eat food, various snacks, ceremonial facilities and many more.The average number of visitors each day is estimated at around 150 to 500 visitors. Based on the results of observations made in traditional markets, the market health conditions are still poor, unhealthy market conditions will cause discomfort for visitors who come to the market.Priority problems that need to be resolved, knowledge and behavior of managers and traders about healthy markets need to be improved, arrangement of market bathrooms / toilets for both visitors and managers, handling market waste management and improving hand washing facilities are not yet available for managers and visitorsThe service method is by observing traditional markets in Mengwi District. Conducting an assessment prior to treatment service to the health level of traditional markets. After the dedication was carried out, an assessment was made of the health of the market. The target audience for managers, traders and visitors to traditional markets with work procedures. Before and after mentoring, healthy market infection was carried out using a form of the Indonesian Minister of Health No. 519 / Menkes / SK / VI / 2008 at traditional markets in Mengwi District.Community service activities are carried out within three months, starting from initial data collection, mentoring to healthy markets and evaluation of activities. Achievements of targets and outputs are in the form of booklets, IPR reports and scientific articles, for 2020 target output booklets, 2021 IPR for community service reports and scientific articles for 2021 output targets. . In addition to providing educational assistance to traders through booklet media, medical masks were also delivered in the context of implementing health protocols to traders in preventing the Covid-19 pandemic. Handover of portable sinks to educate traders and visitors to wash their hands at any time in the context of preventing Covid 19 and handing over trash cans for clean and healthy living habits for visitors, traders, and managers to create a healthy traditional market. There was an increase in the market health score from 6249 to 7109.Keywords: Healthy Traditional Market